Obesity and Stunting in Childhood. Do Grandparents Play A Role? A Systematic Review - Rizki Agustin Purwaningtyas; Ardila Lailatul Barik; Dwi Astuti (Jurnal Ners, 2019)
Introduction: Obesity and stunting in childhood has become one of the greatest global health challenges. The impact of this issue is serious and lasting for individuals, their families, communities and countries. Most of the studies on child weight status have only focused on the mother as the primary caregiver, whereas the role and inﬂuence of the grandparents has received less attention. Grandparent-provided child care has become a trend in many countries, with reported rates of approximately 40% to 58%. The objective of this systematic review was to analyze whether children become stunted or obese when they are cared for by their grandparents.Methods: The methodological search of the literature was conducted using Scopus, Science Direct, PubMed, Pro Quest and ResearchGate, and it was undertaken using PRISMA guidelines. The search identified 1803 papers and 135 full-text articles were screened for eligibility. Finally, 15 met the inclusion criteria. The keyword chain was as follows: ("obesity" OR "stunting") AND (“children”) AND (“grandparents”).Results: As grandparents take on increasingly responsible roles in the lives of their grandchildren, there is an influence on the higher risk of child obesity rather than stunting.Conclusion: In future, nurses should target not only the mother but also the grandparents to control their child’s health, especially when related to their weight status.